Konsepsi Ganti Kerugian Bagi Anak Korban Dalam Tindak Pidana Perdagangan Orang Berdasarkan Nilai Keadilan - M. Arief Kurniawan; Triono Eddy; Adi Mansar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Children are a gift from God that is inseparable from the survival of a nation, so their existence must be protected from everything that can damage them physically or mentally. Children who are victims of criminal acts of human trafficking should be treated like victims who should be protected by the government through existing laws and regulations so that child victims are no longer victims in a legal process with its various dynamics. Compensation for child victims in criminal acts of human trafficking based on the value of justice is realized through compensation. Compensation from the state is given in the event that the perpetrator of the crime of trafficking in persons is unable to pay restitution and the victim is a child, then the restitution can be replaced by providing compensation from the state to the child victim. Furthermore, with the concept of compensation in the form of compensation for child victims, reconstruction of article 48 of Law no. 21 of 2007 concerning the Eradication of the Crime of Human Trafficking, namely the addition of paragraph 8 (eight) in article 48 which states: "In the event that the perpetrator of the criminal act of human trafficking is unable to pay restitution while the victim is a child, the restitution can be replaced by providing compensation from the state towards the victim's children or their heirs